2010
DOI: 10.1016/j.ydbio.2010.08.040
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish Nkd1 promotes Dvl degradation and is required for left–right patterning

Abstract: The establishment of the left-right (LR) axis in zebrafish embryos relies on signals from the dorsal forerunner cells (DFC) and the Kupffer’s vesicle (KV). While the Wnt signaling network influences many aspects of embryonic development, its precise role in LR patterning is still unclear. One branch of the Wnt network leads to stabilization of β-catenin and activation of downstream target genes. Other Wnt ligands appear to act independently of β-catenin to modulate calcium release and influence cell polarity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(80 citation statements)
references
References 64 publications
3
74
3
Order By: Relevance
“…These data together indicate that -catenin signaling pathway is required for charon expression around the KV and this function is mainly mediated by ctnnb1 rather than ctnnb2. Recently, charon expression has been found to be transiently biased on the right side of KV in zebrafish embryos from 8-to 10-somite stages (Schneider et al, 2010). We found that knockdown of either ctnnb1 or ctnnb2 in DFCs did not significantly change the ratio of embryos with a right-side biased charon expression at the six-and 13-somite stages (data not shown).…”
Section: Research Articlementioning
confidence: 47%
See 3 more Smart Citations
“…These data together indicate that -catenin signaling pathway is required for charon expression around the KV and this function is mainly mediated by ctnnb1 rather than ctnnb2. Recently, charon expression has been found to be transiently biased on the right side of KV in zebrafish embryos from 8-to 10-somite stages (Schneider et al, 2010). We found that knockdown of either ctnnb1 or ctnnb2 in DFCs did not significantly change the ratio of embryos with a right-side biased charon expression at the six-and 13-somite stages (data not shown).…”
Section: Research Articlementioning
confidence: 47%
“…In the past few years, studies in mouse and zebrafish have demonstrated that downregulation of several Wnt pathway components,e.g. zebrafish wnt3,wnt8,axin1,apc,gsk3b and nkd1 and mouse Wnt3a, disrupts normal LR development (Carl et al, 2007;Lin and Xu, 2009;Lee et al, 2007;Schneider et al, 2010;Nakaya et al, 2005). However, it is not clear whether and how endogenous -catenin affects LR asymmetry of vertebrate embryos.…”
Section: Endogenous -Catenin Is Required For Normal Laterality Develmentioning
confidence: 99%
See 2 more Smart Citations
“…In Xenopus, Coco is the ortholog of Cerl2 and is the gene thought to respond earliest to leftward flow; it thus manifests asymmetric expression around the organizer and plays a role similar to that of Cerl2 (Schweickert et al, 2010), although histone deacetylase activity at earlier stages might be involved in epigenetic silencing of Nodal (Carneiro et al, 2011). In zebrafish and Medaka, Charon (Dand5 -Zebrafish Information Network), an ortholog of mouse Cerl2, is asymmetrically expressed (R>L) in KV and is indispensable for left and right asymmetry (Hashimoto et al, 2004;Schneider et al, 2010; Hojo et al, 2007;Lopes et al, 2010). Asymmetric signal generated in the node is transmitted to the surrounding tissues.…”
mentioning
confidence: 99%